2018
DOI: 10.1136/bcr-2018-225040
|View full text |Cite
|
Sign up to set email alerts
|

Unusual ocular manifestations following viper bite

Abstract: We report a case of a 70-year-old farmer admitted for viper bite who presented with bilateral hyphema and angle closure attack. He was managed conservatively with topical steroids and cycloplegics. He responded well and was discharged after 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Since the cornea and lens are avascular tissues, snake venoms do not directly injure these tissues. However, some anterior segment complications such as corneal striae, cataract, anterior pseudohypopyon, anterior ischemia, and iris atrophy were also observed in the eye of snakebite victims [ 35 , 36 ]. These complications in the anterior segment might be attributed to the secondary inflammatory effects in the posterior segment.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Since the cornea and lens are avascular tissues, snake venoms do not directly injure these tissues. However, some anterior segment complications such as corneal striae, cataract, anterior pseudohypopyon, anterior ischemia, and iris atrophy were also observed in the eye of snakebite victims [ 35 , 36 ]. These complications in the anterior segment might be attributed to the secondary inflammatory effects in the posterior segment.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…The vast majority of terrestrial snake bites were attributed to the Russel viper [ 22 , 23 , 25 , 27 , 28 , 35 ], with bites resulting from cobras [ 22 , 23 , 27 , 28 , 35 ] or green pit vipers [ 23 , 27 , 28 , 35 ] also fairly common, alongside a low level of bites from other species [ 22 , 23 , 35 ]. The acute symptoms that developed following a terrestrial snake bite differed between species, but reported symptoms included pain [ 23 , 25 ], vomiting [ 23 , 25 ], nausea [ 23 ], localised swelling [ 23 ], acute kidney injury [ 23 , 28 ], necrosis [ 25 ], lymphadenopathy [ 23 ], ocular manifestations [ 29 ] and effects of neurotoxicity [ 20 , 21 ]. Conjunctivitis following the introduction of venom to the eyes by the spitting cobra has also been documented as an outcome [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…ocular manifestations [29] and effects of neurotoxicity [20,21]. Conjunctivitis following the introduction of venom to the eyes by the spitting cobra has also been documented as an outcome [26].…”
Section: Resultsmentioning
confidence: 99%